2008
DOI: 10.3858/emm.2008.40.1.109
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of mitochondrial DNA up-regulates the expression of MDR1 gene via an increase in mRNA stability

Abstract: The mutation and reduction of mitochondrial DNA (mtDNA) have been suggested as factors in the carcinogenesis. However, whether the depletion of mtDNA induces multidrug resistance in cancer cells has not been fully investigated. To elucidate the association of cellular mtDNA content and drug resistance, we generated HCT-8 colon cancer cells which revealed a marked decrease in cellular mtDNA and ATP content, concomitant with a lack of mRNAs encoded by mtDNA. The mtDNA-depleted cells showed a decreased sensitivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 33 publications
(43 reference statements)
3
31
0
Order By: Relevance
“…Several studies have presented evidence that mtDNA plays an important role in cellular sensitivity to cancer therapies (36). We and others have suggested that the mitochondrion could be the integrator of many signals that have a potential effect on tumor-related growth (13,19,36,(51)(52)(53)(54). Little is known however about the effect of long term exposure of an alkylating agent on mtDNA copy number and heteroplasmy in cancer cells, One possible explanation for the decreased mtDNA copy number is that expression of DNA polymerase-␄, the polymerase responsible for the replication and repair of mtDNA, is substantially reduced in TMZ-resistant cells, impairing replication of the mitochondrial genome.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have presented evidence that mtDNA plays an important role in cellular sensitivity to cancer therapies (36). We and others have suggested that the mitochondrion could be the integrator of many signals that have a potential effect on tumor-related growth (13,19,36,(51)(52)(53)(54). Little is known however about the effect of long term exposure of an alkylating agent on mtDNA copy number and heteroplasmy in cancer cells, One possible explanation for the decreased mtDNA copy number is that expression of DNA polymerase-␄, the polymerase responsible for the replication and repair of mtDNA, is substantially reduced in TMZ-resistant cells, impairing replication of the mitochondrial genome.…”
Section: Discussionmentioning
confidence: 99%
“…49 Moreover, depletion of mtDNA in human hepatoma SK-Hep1 cells results in an adaptive increase in the expression of manganese superoxide dismutase (MnSOD) and other antioxidant enzymes that enabled the cancer cells to counteract oxidative stress or chemotherapeutic agents. 50 The depletion of mtDNA was also shown to increase the expression of the multidrug resistance 1 (MDR1) gene and hence to exhibit higher tolerance to anti-cancer agents in human colon cancer HCT-8 cells, 51 osteosarcoma 143B cells, 52 and hepatoma cells. 53 Chloramphenicol-induced mitochondrial stress in human hepatoma HepG2 cells and non-small cell lung cancer H1299 cells increases p21 expression and prevents mitomycin-induced apoptosis through a p21-dependent pathway.…”
Section: Mitochondrial Dysfunction Induced By Somatic Mtdna Alteratiomentioning
confidence: 99%
“…For Western blot analysis, an equal amount of protein was subjected to electrophoresis on SDS-polyacrylamide gel and transferred to a nitrocellulose membrane (Schleicher & Schuell, Keene, NH) by electroblotting. Blots were probed with the desired antibodies for 1 h, incubated with the diluted enzyme-linked secondary antibodies, and visualized by enhanced chemiluminescence (ECL) Western blotting detection reagents (SuperSignal, Thermo scientific, Rockford, IL) according to the recommended procedure (31).…”
Section: Methodsmentioning
confidence: 99%